Все уже решено, нужно только обьяснение. , надо.

Кирилл727383 Кирилл727383    2   08.09.2019 20:25    0

Ответы
DimaNewPARK DimaNewPARK  07.10.2020 01:41

= 6×√2

Объяснение:

4 \times \sqrt{2} - 3 \times \sqrt{8} + 2 \times \sqrt{32} =

= 4 \times \sqrt{2} - 3 \times \sqrt{4 \times 2} + 2 \times \sqrt{16 \times 2} =

= 4 \times \sqrt{2} - 3 \times \sqrt{4} \times \sqrt{2} + 2 \times \sqrt{16} \times \sqrt{2} =

4 \times \sqrt{2} - 3 \times 2 \times \sqrt{2} + 2 \times 4 \times \sqrt{2}

= 4 \times \sqrt{2} - 6 \times \sqrt{2} + 8 \times \sqrt{2} =

= \sqrt{2} \times (4 - 6 + 8) = \sqrt{2} \times 6 = 6 \times \sqrt{2}

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра